EFEKTIVITAS PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR PEDESAAN (Studi Di Desa Baturapa Kecamatan Lolak Kabupaten Bolaang Mongondow) - SUSANTO, INRIA CHRISTY; ROMPAS, WELSON; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2021)
To be able to make a peaceful, educated and prosperous village as the vision of the villagegovernment, the development of infrastructure which is an infrastructure based on a productive agriculturaleconomy is a priority. Various infrastructure developments have been carried out by maximizing existingfunds both from village fund programs and through community self-help. The purpose of this study is to findout how the effectiveness of the implementation of rural infrastructure development, especially in BaturapaVillage, Lolak District, Bolaang Mongondow Regency is. The research method used in this study is aqualitative method. Informants in research are people who can provide information about the situation andcondition of the research setting. The focus of the research is seen from the indicators according to Makmur,namely the accuracy of the use of the budget, the accuracy of the use of human resources and the accuracyof the use of time. Data collection techniques through interviews, observation and use of documents. Theresults of the study show the effectiveness of implementing rural infrastructure development, especially inBaturapa Village, Lolak District, Bolaang Mongondow Regency until now it can be seen that efforts to buildinfrastructure based on a productive agricultural economy that have been set as village planning documentshave not been achieved and in the use of timing non-conforming causes a change in the disbursementschedule.Keywords : Effectiveness, Development, Rural Infrastructure